Three-dimensionally phosphatized meiofaunal bivalved arthropods from the Upper Cambrian of Western Hunan, South China - Zhang, Huaqiao; Xiao, Shuhai (Neues Jahrbuch für Geologie und Paläontologie - Abhandlungen, 2017)
Meiofaunas are important ecological players in modern marine ecosystems, but their Cambrian fossil record is rather poor, even in some of the best-known Lagerstatten, such as the Burgess Shale biota, which are typically dominated by macroscopic animals. In this regard, the Upper Cambrian Wangcun Lagerstatte in South China is unusual in its richness in meiofaunal animals. Here, we described new material of three-dimensionally phosphatized meiofaunal bivalved arthropods from a single horizon in the Paibian Stage, Furongian Series of Wangcun section, Western Hunan, South China. New bivalved arthropods include Albrunnicola bengtsoni (bradoriid), Mengdongella elliptica gen. et sp. nov., and an indeterminate phosphatocopine Gen. et sp. indet. The new discovery extends the stratigraphic and geographic ranges of A. bengtsoni, which was previously only known from Lower Cambrian strata of Australia and Antarctic. The shield of A. bengtsoni bears pits that might have facilitated respiration or sensing. Mengdongella elliptica is a new bivalved arthropod of uncertain affinity, with antero-dorsal spines functioning as sensory organs. These new findings highlight the importance of the Orsten-type taphonomic window in revealing the diversity of meiofaunal ecdysozoans in Cambrian oceans.